Qualidade do preenchimento da caderneta de saúde da criança - Leal, Sheila Lúcia Serpa (2021)
The monitoring of the child's growth has its longitudinality of care in Primary Health Care according to the childcare calendar provided by the Ministry of Health. Throughout the Brazilian territory, we have the Caderneta de Saúde da Criança (CSC), a child health booklet, for recording growth trends and its correct use is a valuable action for observing children in vulnerable situations. This dissertation aims to discuss the monitoring of the growth of children in Brazil and in João Pessoa, Paraíba, based on the observation of the use of CSC by Primary Health Care´s professionals. Thus, there was: i) a Systematic Literature Review on filling the growth curves of CSC in Brazil and ii) a cross-sectional analytical observational study on the use of the instrument in the city of João Pessoa and possible correlations with nutritional deviations. Fifteen articles were included and studied in the Literature Review, all showing unsatisfactory booklet´s filling, thus revealing the weakness in the use of this instrument. The observational analysis carried out locally also corroborated the need for investment in training and awareness of health professionals and the population on the importance of the proper use of CSC, considering that only for the weight-for-age curve of the second year of life, a percentage of adequate filling greater than 50% was found. Without intending to end the discussion, the present study hopes to collaborate to recognize the indispensability of CSC for comprehensive care and health promotion for Brazilian children.